Effect of Nozzle Pressure and Shape Ratios on Gas Flow of a 122 mm Supersonic Rocket Nozzle investigated by CFD - Chaiaiad, Chatchapat; Thongsri, Jatuporn (My University, 2023)
This article reports the effect of nozzle pressure ratio (NPR) and shape ratio (SR) on the gas flow of a 122 mm supersonic rocket, a convergent-divergent nozzle, using computational fluid dynamics (CFD). The NPR is the ratio between the pressure inlet and outlet, while the SR is the ratio between the outlet and throat areas of the nozzle. The CFD results revealed the gas flow, pressure (P), Mach number (M), temperature (T), shock, and jet for some conditions of NPR and SR, consistent with the theory. Furthermore, it was found that M increased with increasing NPR and/or SR. Furthermore, T enhanced with increasing NPR but decreased with increasing SR. This report can be used to further development of this nozzle type suitable for missions.
Keywords: 122 mm nozzle; computational fluid dynamics; computer simulation; convergent-divergent nozzle; de Laval nozzle; supersonic rocket